Paper planes, don't always soar - the project book - Tan, Terry De Hao (Nanyang Technological University, 2023)
Inspired by a true story of an aviation disaster, a daughter tries to bridge the bond she lost after her father returns home from a plane crash, where he struggles to remember his life before that fateful catastrophe.